The Impact of Centralization on the Enactment of Law Number 4 of 2009 concerning Mineral and Coal Mining on the Development of Regional Autonomy - V Zahry, Sarkowi (Borong Newinera Publisher, 2023)
The condition of illegal coal mines has been going on for a long time in East Kalimantan Province at the same time when mining business permits (IUP) from district and city governments have been issued since the 2000s, as well as several small islands where there are explicit illegal mines. This unlicensed coal mining was originally carried out by traditional miners, but it has evolved due to factors such as poverty, lack of employment, and lack of opportunities. Based on the description above, it is to find out the centralization arrangement of the enactment of Law Number 4 of 2009 concerning Mineral and Coal Mining on the development of regional autonomy. This study uses an empirical juridical (sociological) approach which is research to describe and analyze existing problems and is included in the type of library research that will be presented descriptively. In the process of making policies, it is important for communities to participate and fulfill their aspirations so that the use of natural resources can improve the mineral and coal mining sector and improve the welfare of the community. Then, the government should consider strategic and potential matters, especially those related to the environment. One consequence of the centralization of mining is that local governments no longer have the authority to control mineral and coal mining. In addition, local governments face distortions of oversight of mining management and declining regional revenues.